2016
DOI: 10.7150/ijms.10539
|View full text |Cite
|
Sign up to set email alerts
|

Impact of JAK2V617F Mutation Burden on Disease Phenotype in Chinese Patients with JAK2V617F-positive Polycythemia Vera (PV) and Essential thrombocythemia (ET)

Abstract: Most patients with polycythemia vera (PV) and half of essential thrombocythemia (ET) possess an activating JAK2V617F mutation. The objective of this study was to better define the effect of JAK2V617F mutant allele burden on clinical phenotypes in Chinese patients, especially thrombosis. By real-time polymerase chain reaction (RT-PCR), the JAK2V617F mutation burden was detected in 170 JAK2V617F-positive patients, including 54 PV and 116 ET. The results showed that JAK2V617F allele burden was higher in PV than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
(47 reference statements)
3
17
0
1
Order By: Relevance
“…This is in line with a study from the West by Tefferi et al; however, Zhao et al did not find any effect of age in Chinese population. [8,21] We observed that the patients with splenomegaly had significantly higher JAK2V617F allele burden as compared to patients without splenomegaly (P < 0.017). Our results are in concordance with the study conducted by Vannucchi et al in Italian population and Zhao et al in Chinese population.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This is in line with a study from the West by Tefferi et al; however, Zhao et al did not find any effect of age in Chinese population. [8,21] We observed that the patients with splenomegaly had significantly higher JAK2V617F allele burden as compared to patients without splenomegaly (P < 0.017). Our results are in concordance with the study conducted by Vannucchi et al in Italian population and Zhao et al in Chinese population.…”
Section: Discussionmentioning
confidence: 74%
“…Our results are in concordance with the study conducted by Vannucchi et al in Italian population and Zhao et al in Chinese population. [11,21] However, Tefferi et al did not find any correlation of allele burden with splenomegaly. [12] The impact of JAK2V617F mutation on thrombosis is reported to be controversial in MPN patients.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, ASXL1 mutations include not only point mutations, but frameshifts and nonsense mutations, of which the most common ones are frameshift mutations (c.1934dupG), accounting for nearly 50% of the reported ASXL1 mutations ( 14 16 ). Furthermore, in patients with ET, the frequency of Janus kinase (JAK)2 V617F, calreticulin (CALR) and myeloproliferative leukemia (MPL) W515 mutations was reported to be ~50, <5 and ~11% in Western countries ( 17 20 ) and ~60, ~30 and <5% in China, respectively ( 21 23 ). However, the occurrence and precise roles of ASXL1 mutations in Chinese ET patients have remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular diagnosis of PV was made possible after discovery of V617F a gain of function mutation in janus kinase 2 gene 2 which is now an important criterion to identify Philadelphia negative myeloproliferative neoplasms (Ph -ve MPNs) 3 . This mutation is found in majority (95%) of polycythemia vera patients, leading to constitutive tyrosine kinase phosphorylation inducing cytokine hypersensitivity and erythrocytosis 4 - 7 . JAK2 is part of the janus kinase family having 7 JAK homology domains (JH1-JH7).…”
Section: Introductionmentioning
confidence: 99%